Climate Change and Environmental Sustainability Volume 6 - He, Baojie; Sharifi, Ayyoob; Feng, Chi; Yang, Jun (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This volume of Climate Change and Environmental Sustainability covers topics on green finance and investment, collaboration building and public engagement, and industry governance towards carbon neutrality and environmental sustainability. First, it presents issues related to embodied carbon in the international trade, impacts of the green finance system on carbon emissions, the implementation of green deal strategies, linkage between foreign direct investment and carbon emissions, and the implications of COVID-19 for decarbonisation actions. Following such critical problems, theoretical conceptualisation of new green deals, international research team collaboration for sustainability, nature conservation communication in social networks, and the efficiency of environmental policies in emission reduction are discussed. Next, close attention is paid to various industries, including agriculture, tourism, and manufacturing, by analysing topics relevant to the impacts of climate-related factors, assessment indicator systems or appraisal systems, and value chain systems. In addition, the book also presents disaster risk mapping studies for assessing vulnerability, best practices of risk management, and cases on environment-induced impacts on health. Results reported in this book are conducive to a better understanding of green finance and investment regimes, community engagement, and industry sustainability. We expect the book to benefit decision-makers, practitioners, and researchers in different fields and contribute to carbon neutrality and economic growth.